Trace Analysis in End-Exhaled Air Using Direct Solvent Extraction in Gas Sampling Tubes: Tetrachloroethene in Workers as an Example - Chris-Elmo Ziener; Pia-Paulin Braunsdorf (International Journal of Analytical Chemistry)
Simple and cost-effective analytical methods are required to overcome the barriers preventing the use of exhaled air in routine occupational biological monitoring. Against this background, a new method is proposed that simplifies the automation and calibration of the analytical measurements. End-exhaled air is sampled using valveless gas sampling tubes made of glass. Gaseous analytes are transferred to a liquid phase using a microscale solvent extraction performed directly inside the gas sampling tubes. The liquid extracts are analysed using a gas chromatograph equipped, as usual, with a liquid autosampler, and liquid standards are used for calibration. For demonstration purposes, the method’s concept was applied to the determination of tetrachloroethene in end-exhaled air, which is a biomarker for occupational tetrachloroethene exposure. The method’s performance was investigated in the concentration range 2 to 20 μg tetrachloroethene/L, which corresponds to today’s exposure levels. The calibration curve was linear, and the intra-assay repeatability and recovery rate were sufficient. Analysis of real samples from dry-cleaning workers occupationally exposed to tetrachloroethene and from nonexposed subjects demonstrated the method’s utility. In the case of tetrachloroethene, the method can be deployed quickly, requires no previous experiences in gas analysis, provides sufficient analytical reliability, and addresses typical end-exhaled air concentrations from exposed workers.